An alternative vision for Malaysia - Jeyakumar Devaraj (Strategic Information and Research Development Centre, 2015)
The author, a qualified medical practitioner, turned to politics after 18 years in Government service and founded the Parti Sosialis Malaysia with others. He is noted for having wrested the parliamentary seat of the leader of the Malaysian Indian Congress, a member of the ruling Government coalition and having held the seat in a subsequent election. This is a collection of his speeches, papers and letters. 135 pages.